Shared prosperity Vision 2030 - Wan Salim, Wan Wardatul Amani (Ministry of Economic Affairs, Malaysia., 2019)
Shared Prosperity Vision 2030 is a commitment to make Malaysia a nation that achieves sustainable growth along with fair and equitable distribution, across income groups, ethnicities, regions and supply chains. The commitment is aimed at strengthening political stability, enhancing the nation’s prosperity and ensuring that the rakyat are united whilst celebrating ethnic and cultural diversity as the foundation of the nation state.